PENGARUH AUDIT TENURE, KOMISARIS INDEPENDEN, DAN FINANCIAL DISTRESS TERHADAP INTEGRITAS LAPORAN KEUANGAN - Sabilla Putri, Fiddinina; Shanti, Yunita Kurnia (JURNAL AKUNTANSI BARELANG, 2024)
ABSTRACT This research aims to empirically prove the influence of Audit Tenure, Independent Commissioners, and Financial Distress on the Integrity of Financial Statements. In this research, the independent variables used are Audit Tenure, Independent Commissioner, and Financial Distress, while the dependent variable used is Financial Report Integrity. This research was conducted by taking a sample of primary consumer goods sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The type of data used in this research is secondary data in the form of financial reports that have been audited and published on the Indonesia Stock Exchange (BEI) from 2018-2022. The samples were collected using a purposive sampling method with the number of companies sampled being 36 companies with a research period of 5 years, so that 180 data were obtained. Power processing using the Microsoft Office Excel program and the Eviews 12 statistical program by analyzing descriptive statistics, model suitability tests, classical assumption tests, coefficient of determination, panel data regression analysis, F statistical tests, and T statistical tests. The results of this research show that: (1) Audit Tenure, Independent Commissioners, and Financial Distress have a simultaneous effect on the Integrity of Financial Statements, (2) Financial Distress has a positive effect on the Integrity of Financial Reports, (3) Audit Tenure has no effect on the Integrity of Financial Reports, (4) Independent Commissioners have no effect to the Integrity of Financial Statements. Keywords: Audit Tenure, Independent Commissioner, Financial Distress, Integrity of Financial Statements